2008
DOI: 10.1038/sj.bjc.6604201
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology of cancer therapies in older adults

Abstract: This abbreviated review outlines the physiologic changes associated with aging, and examines how these changes may affect the pharmacokinetics and pharmacodynamics of anticancer therapies. We also provide an overview of studies that have been conducted evaluating the pharmacology of anticancer therapies in older adults, and issue a call for further research. (Yancik and Ries, 2000). As the general population ages and life expectancy increases, the number of older adults with cancer is growing.Several unique c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 51 publications
(46 reference statements)
0
45
0
2
Order By: Relevance
“…Agerelated pharmacokinetic and pharmacodynamic changes can lead to increased organ toxicity and therefore enhanced defluvium capillorum [24]. For doxorubicin and weekly application of taxane, an age-related lower renal clearance was found [24].…”
Section: Discussionmentioning
confidence: 99%
“…Agerelated pharmacokinetic and pharmacodynamic changes can lead to increased organ toxicity and therefore enhanced defluvium capillorum [24]. For doxorubicin and weekly application of taxane, an age-related lower renal clearance was found [24].…”
Section: Discussionmentioning
confidence: 99%
“…It still remains under debate whether standard chemotherapies established by pivotal phase III trials might also be applicable to elderly patients with advanced gastric cancer [20][21][22][23]. Lee et al [24] conducted a randomized phase II study comparing capecitabine and S-1 in patients older than 65 years, and showed satisfactory effi cacy of S-1 (RR, 29%; median time to progression, 4.2 months; median OS, 8.1 months).…”
Section: Discussionmentioning
confidence: 99%
“…The kidney is a very common route for the excretion of drugs; however, it is reported that the glomerular fi ltration rate generally decreases by approximately 0.75 ml/min per year after the age of 40, on average [26]. In several pharmacokinetic studies of chemotherapeutic drugs, such as paclitaxel, vinorelbine, etoposide, cisplatin, and doxorubicin, an age-related decrease in creatinine clearance has been reported [23].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric motility slows down and the secretion of gastric juices decreases [126]. Cancer is generally considered to be a disease of the elderly, with 60% of the diagnoses of cancer taking place in patients aged 75 and over [127]. Although age-induced F alterations seem possible, literature and registration texts do not report the necessity of adjusting the dose of smTKIs for the elderly [11][12][13].…”
Section: Elderlymentioning
confidence: 99%